2018
DOI: 10.1002/cbf.3316
|View full text |Cite
|
Sign up to set email alerts
|

ILEI is an important intermediate participating in the formation of TGF‐β1–induced renal tubular EMT

Abstract: There is no study reporting the effect of ILEI in renal EMTs. In this research, we examined the role and mechanism of ILEI in EMT using tubular epithelial cell; we found that ILEI participated in renal tubular EMT, and overexpression of ILEI can not only induce EMT of HK-2 cells independently but also enhance EMT in response to TGF-β1. Meanwhile, we found ILEI small interfering RNA blocked the EMT induced by TGF-β1, and ILEI participates in the EMT caused by TGF-β1 via ERK and Akt signalling pathways. We hoped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Although ILEI has been thoroughly described as a tumor autonomous regulator of EMT and invasion, the role of ILEI in paracrine signaling is still unclear ( 25 , 28 , 29 , 33 , 43 45 ). Our characterization of the novel vemurafenib–USF-1–ILEI regulatory axis has implications for paracrine ILEI signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Although ILEI has been thoroughly described as a tumor autonomous regulator of EMT and invasion, the role of ILEI in paracrine signaling is still unclear ( 25 , 28 , 29 , 33 , 43 45 ). Our characterization of the novel vemurafenib–USF-1–ILEI regulatory axis has implications for paracrine ILEI signaling.…”
Section: Resultsmentioning
confidence: 99%
“…In the renal tubular cell line HK2, FAM3C can independently induce EMT via the Akt-signaling pathway. Knockdown of FAM3C enhances the expression of E-cadherin and suppresses the phosphorylation of Akt 8. FAM3C overexpression has been reported to induce Akt phosphorylation in HepG2 cells 9.…”
Section: Introductionmentioning
confidence: 99%
“…More and more evidences showed that EMT is a typical feature of renal fibrosis, and EMT of tubular epithelial cells contributes significantly to the occurrence, development, and pathological processes of kidney fibrosis (Sharma, 2014;Sun et al, 2017). Transforming growth factor-β1 (TGF-β1) is a typical pro-fibrotic cytokine involved in the process of EMT (Zhao et al, 2018). Studies had shown that TGF-β1 participates in the EMT process by activating the TGF-β1/Smad signaling pathway (Du et al, 2015).…”
Section: Introductionmentioning
confidence: 99%